Geographies of UK flooding in 2013/4. Issue 4 (December 2014) - Thorne, Colin
<x xml:space="preserve">Abstract</x> Between December 2013 and February 2014, an extreme storm surge, a series of intense storms, and the cumulative effects of heavy and persistent rainfall caused widespread flooding throughout the UK, prompting renewed public and scientific debates on who, or what, might be to blame. The public divided fairly evenly into two diametrically opposed groups, the first blaming the government (who initially responded by trying to shift blame to their expert advisors), attributing the mounting flood losses and prolonged misery to lack of investment in flood defences and river dredging. The second group blamed farmers for over‐intensive agriculture in upstream catchments, inappropriate development in floodplains, and poor judgement on the part of the victims in choosing to live, work or farm in areas vulnerable to inundation. The floods resulted from a protracted sequence of deep, Atlantic depressions that followed a more southerly track than usual due to the position and configuration of the planetary jet stream. This prompted a second, no less polarised, scientific debate concerning whether the meteorological characteristics of the floods provided evidence that climate change has started to influence not only the probability of UK flooding, but also its nature, spatial distribution and duration. Both debates are intrinsically geographical, and this commentary sets out how understanding the geographies of flooding can help frame and inform them. This is addressed through consideration of these geographies, characterised as physical, rural, urban, social, economic and political. While an individual event (or even a sequence clustered of floods) cannot alone prove anything, the winter floods reinforce the conclusions of the Government's Flood Foresight study, which was commissioned in response to the 2000 (Millennium) Floods and updated following nationwide floods in summer 2007.